Anatomical Organization of Urocortin 3-Synthesizing Neurons and Immunoreactive Terminals in the Central Nervous System of Non-Human Primates [Sapajus spp.] - Battagello, Daniella S.; Diniz, Giovanne B.; Candido, Paulo L.; da Silva, Joelcimar M.; de Oliveira, Amanda R.; Torres da Silva, Kelly R.; Lotfi, Claudimara F. P.; de Oliveira, José A.; Sita, Luciane V.; Casatti, Cláudio A.; Lovejoy, David A.; Bittencourt, Jackson C. (Frontiers in Neuroanatomy, 2017)
Urocortin 3 (UCN3) is a neuropeptide member of the corticotropin-releasing factor (CRF) peptide family that acts as a selective endogenous ligand for the CRF, subtype 2 (CRF2) receptor. Immunohistochemistry and in situ hybridization data from rodents revealed UCN3-containing neurons in discrete regions of the central nervous system (CNS), such as the medial preoptic nucleus, the rostral perifornical area (PFA), the medial nucleus of the amygdala and the superior paraolivary nucleus. UCN3-immunoreactive (UCN3-ir) terminals are distributed throughout regions that mostly overlap with regions of CRF2 messenger RNA (mRNA) expression. Currently, no similar mapping exists for non-human primates. To better understand the role of this neuropeptide, we aimed to study the UCN3 distribution in the brains of New World monkeys of the Sapajus genus. To this end, we analyzed the gene and peptide sequences in these animals and performed immunohistochemistry and in situ hybridization to identify UCN3 synthesis sites and to determine the distribution of UCN3-ir terminals. The sequencing of the Sapajus spp. UCN3-coding gene revealed 88% and 65% identity to the human and rat counterparts, respectively. Additionally, using a probe generated from monkey cDNA and an antiserum raised against human UCN3, we found that labeled cells are mainly located in the hypothalamic and limbic regions. UCN3-ir axons and terminals are primarily distributed in the ventromedial hypothalamic nucleus (VMH) and the lateral septal nucleus (LS). Our results demonstrate that UCN3-producing neurons in the CNS of monkeys are phylogenetically conserved compared to those of the rodent brain, that the distribution of fibers agrees with the distribution of CRF2 in other primates and that there is anatomical evidence for the participation of UCN3 in neuroendocrine control in primates.